Discourses of Feminism and Modernism in the Essays of Julka Chlapec Đorđević and Jela Spiridonović-Savić - Đurić, Dubravka (Poznańskie Studia Slawistyczne, 2014)
I start from the definition of Serbian Yugoslav bourgeois culture as a semi-peripheral and having this in mind, I tend to analyze the essays by Julka Chlapec Đorđević and Jela Spiridonović-Savić, from the perspective of the world systemic theories applied to literature.